Peptide nucleic acids targeting β-globin mRNAs selectively inhibit hemoglobin production in murine erythroleukemia cells - MONTAGNER, GIULIA (Int J Mol Med, 2015)
In the treatment of hemoglobinopathies, amending altered hemoglobins and/or globins produced in excess is an important part of therapeutic strategies and the selective inhibition of globin production may be clinically beneficial. Therefore the development of drug-based methods for the selective inhibition of globin accumulation is required. In this study, we employed peptide nucleic acids (PNAs) to alter globin gene expression. The main conclusion of the present study was that PNAs designed to target adult murine β-globin mRNA inhibit hemoglobin accumulation and erythroid differentiation of murine erythroleukemia (MEL) cells with high efficiency and fair selectivity. No major effects were observed on cell proliferation. Our study supports the concept that PNAs may be used to target mRNAs that, similar to globin mRNAs, are expressed at very high levels in differentiating erythroid cells. Our data suggest that PNAs inhibit the excess production of globins involved in the pathophysiology of hemoglobinopathies.